Meningeal Lymphatics: An Immune Gateway for the Central Nervous System - Gabriel A. Tavares; Antoine Louveau (Cells, 2021)
The recent (re)discovery of the meningeal lymphatic system has opened new theories as to how immune cells traffic and interact with the central nervous system (CNS). While evidence is accumulating on the contribution of the meningeal lymphatic system in both homeostatic and disease conditions, a lot remains unknown about the mechanisms that allow for interaction between the meningeal lymphatic system and immune cells. In this review, we synthesize the knowledge about the lymphatic immune interaction in the CNS and highlight the important questions that remain to be answered.